Lithium supplement composite material and preparation method thereof, positive pole piece, isolating membrane, secondary battery and electric device
Patent Information
- Application Number
- CN202380059462.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-04-04
AI Technical Summary
During the first cycle of lithium-ion energy storage devices, the formation of a solid electrolyte interface at the negative electrode interface causes irreversible capacity loss and a decrease in active lithium content, resulting in a decrease in energy density. The existing pre-lithiation lithium supplementation technology using active metal lithium to supplement lithium is not effective.
A lithium-replenishing composite material is used, including a core and a coating layer. The core is composed of an organic lithium-replenishing agent and a metal catalyst. The coating layer is composed of a conductive material and is synthesized by a recrystallization method. The metal catalyst reduces the decomposition potential of the organic lithium-replenishing agent. , the conductive material coating layer inhibits the dissolution of metal catalysts and optimizes battery cycle performance.
It achieves excellent lithium replenishment performance, improves the cycle performance and conductivity of the battery, avoids irreversible damage to the cathode active material at high potential, and extends the service life of the battery.
Smart Images

Figure CN119768936A_ABST
Abstract
Description
Lithium-supplementing composite material and preparation method thereof, positive electrode sheet, separator, secondary battery and electrical device Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium-supplementing composite material and a preparation method thereof, a positive electrode sheet, a separator, a secondary battery, and an electrical device. Background Art
[0002] During the first cycle of lithium-ion energy storage devices, irreversible capacity loss occurs due to the formation of a solid electrolyte interface (SEI) at the negative electrode interface. This reduction in active lithium content leads to a decrease in the energy density of the lithium-ion energy storage device. To address the problem of reduced battery capacity caused by irreversible lithium loss during the first charge and discharge process, pre-lithiation lithium replenishment technology has become the preferred choice among many technologies. Existing pre-lithiation lithium replenishment technologies mainly use active metallic lithium, but the lithium replenishment effect is not good. Technical issues
[0003] The main purpose of this application is to propose a lithium-supplementing composite material and its preparation method, positive electrode plate, isolation membrane, secondary battery and power-consuming device, aiming to provide a lithium-supplementing composite material with good lithium-supplementing effect and optimize the battery's cycle performance. Technical Solutions
[0004] In a first aspect, the present application proposes a lithium-supplementing composite material, comprising a core and a coating layer containing a conductive material disposed outside the core and at least partially covering the core. The core is made of a lithium-supplementing agent and a metal catalyst, and the lithium-supplementing agent comprises an organic lithium-supplementing agent.
[0005] Thus, the material of the core includes an organic lithium replenisher and a metal catalyst. The organic lithium replenisher provides a lithium source for lithium replenishment. During the first cycle of charging of the battery, the organic lithium replenisher releases lithium ions to replenish the negative electrode, and the remaining components are converted into gas and discharged from the battery. There is no residue after the lithium replenishment, which will not affect the mass energy density and subsequent performance of the battery. The presence of the metal catalyst can reduce the decomposition potential of the organic lithium replenisher, thereby allowing the organic lithium replenisher to exert more capacity at a low potential, achieving the lithium replenishment effect while avoiding the irreversible damage of the positive electrode active material structure and the electrolyte by the high potential. The conductive material coating layer is at least partially coated on the outside of the core, which can inhibit the dissolution of metal in the metal catalyst. At the same time, it can also improve the conductive properties of the lithium replenishing composite material, thereby optimizing the cycle performance of the battery. The lithium replenishing composite material proposed in this application has excellent lithium replenishing performance and can optimize the cycle performance of the battery through the coating layer containing the conductive material and the core provided in the coating layer containing the conductive material.
[0006] In some embodiments, the organic lithium supplement includes Li2C2O4, Li2C4O4, Li2C3O5, Li2C4O6, (Li2C2O2N2) n At least one of the organic lithium replenishers, during the first cycle of charging of the battery, releases lithium ions to replenish lithium to the negative electrode, and the remaining components simultaneously generate gases such as carbon monoxide, carbon dioxide, nitrogen or nitrogen oxides, which are discharged from the battery. There is no residue after the lithium replenishment, and it will not affect the mass energy density and subsequent performance of the battery.
[0007] In some embodiments, the metal catalyst comprises at least one of a transition metal oxide, a transition metal nitride, and a transition metal carbide. Transition metals have unfilled valence shell d orbitals, which easily deform their electron clouds. Based on the 18-electron rule, their properties differ significantly from those of other elements. Due to the presence of empty d orbitals, transition metals readily form complexes. Metal elements utilize hybrid orbitals to accept electrons to achieve a stable state of 16 or 18 electrons, making them suitable for use as metal catalysts. Therefore, using at least one of a transition metal oxide, a transition metal nitride, and a transition metal carbide as a metal catalyst exhibits excellent catalytic effects.
[0008] In some embodiments, the transition metal includes at least one of Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, In, W, Zr, Ta and W. The use of at least one of the above transition metals can reduce the decomposition potential of the organic lithium supplement agent, thereby allowing the organic lithium supplement agent to exert more capacity at a low potential, achieving the lithium supplement effect while avoiding the irreversible damage of the positive electrode active material structure and the electrolyte caused by high potential.
[0009] In some embodiments, the conductive coating layer comprises at least one of an organic conductive polymer and conductive carbon. Using such a conductive coating layer can reduce the dissolution of transition metals while enhancing the overall conductivity of the material, thereby improving the battery's lithium replenishment capacity and service life.
[0010] In some embodiments, the material of the coating layer containing the conductive material includes an organic conductive polymer, and the organic conductive polymer includes at least one of polyaniline, polypyrrole, and polythiophene. Polyaniline is a type of conductive polymer material obtained from aniline monomer through chemical oxidation polymerization or electrochemical polymerization. After doping, polyaniline has conductivity, and it also has photoelectric conversion properties and nonlinear optical properties. The electrical activity of polyaniline comes from the π electron conjugated structure in the molecular chain: as the π electron system in the molecular chain expands, the π bonding state and the π* antibonding state form the valence band and conduction band respectively. This non-localized π electron conjugated structure can form P-type and N-type conductive states after doping. Unlike the doping mechanism of other conductive polymers that produce cationic vacancies under the action of oxidants, the number of electrons in the doping process of polyaniline does not change, but is generated by the decomposition of the doped proton acid to produce H + and counter anions (such as Cl - , sulfate, phosphate, etc.) enter the main chain and combine with the nitrogen atoms in the amine and imine groups to form polar and bipolar delocalized into the π bonds of the entire molecular chain, thereby making polyaniline exhibit high conductivity. Polyaniline has the characteristics of high charge storage capacity, good stability to oxygen and water, good electrochemical performance, low density and reversible oxidation / reduction characteristics. It can serve as both a conductive matrix and an active material in composite electrodes. Polypyrrole is a common conductive polymer with high conductivity, good environmental stability, reversible electrochemical redox characteristics and strong charge storage capacity. It is an ideal electrode material for polymer secondary batteries. Polythiophene is a common conductive polymer. The polythiophene obtained by electrochemical polymerization in a boron trifluoride ether complex has a strength greater than that of metallic aluminum. Using at least one of the above organic conductive polymers further reduces metal dissolution and improves conductivity.
[0011] In some embodiments, the material of the coating layer containing the conductive material includes conductive carbon, and the conductive carbon includes at least one of graphene, carbon nanotubes, acetylene black, Super P, Ketjen black and organic-derived carbon. Graphene is a new material in which carbon atoms connected by sp² hybridization are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Graphene has excellent optical, electrical and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine and drug delivery. It is considered to be a revolutionary material in the future; carbon nanotubes, as one-dimensional nanomaterials, are light in weight, have perfect hexagonal structures, and have many abnormal mechanical, electrical and chemical properties; acetylene black is acetylene with a purity of more than 99% obtained by decomposition and purification of by-product gas during pyrolysis of calcium carbide or naphtha (raw gasoline), and is obtained by continuous pyrolysis. Compared with furnace carbon black, its crystallization and secondary structure are more developed, so its conductivity and liquid absorption are also better, with less impurities such as heavy metals and less loss caused by self-discharge; Super P P (SP) is a conductive carbon black prepared by the furnace method (MMM method). It is composed of primary particles (primary structure) with a diameter of about 40nm agglomerated into primary aggregates (secondary structure) of 150-200nm, and then processed through soft agglomeration and artificial compression. The overall shape is grape chain; the role of SP in lithium-ion batteries is more to disperse primary aggregates of 150~200nm around the active material to form a multi-branched conductive network, thereby reducing the physical internal resistance of the battery and improving electronic conductivity; Ketjen black (Ketjen black) is a carbon black produced by a very original special production process. Compared with ordinary conductive carbon black, Ketjen black only needs a very low addition amount to achieve high conductivity, so Ketjen black has always been the best among conductive carbon blacks; using at least one of the above conductive carbons can further reduce metal dissolution and improve conductive performance.
[0012] In some embodiments, the Dv50 particle size of the lithium-supplementing composite material is 2 to 30 μm. If the Dv50 particle size of the lithium-supplementing composite material is too small, the slurry will easily agglomerate and gel, the viscosity will increase, and the solid content will decrease. If the particle size is too large, the polarization of the lithium ion release reaction in the lithium-supplementing agent will increase, thereby reducing the lithium-supplementing efficiency. When the particle size is above, it is conducive to fully exerting the lithium-supplementing performance and optimizing the cycle performance of the battery. The Dv50 particle size of the metal catalyst is 0.1 to 10 μm. If the particle size is too small, the synthesis is difficult and not conducive to industrialization, and it is easy to cause the stability of the catalytic material itself to deteriorate; if the particle size is too large, the catalytic activity of the metal catalyst will be weakened. The thickness of the coating layer containing the conductive material is 2 to 100 nm, and the thickness of the coating layer containing the conductive material directly affects the coating performance. If the conductive material coating layer of the composite lithium supplement shell is too thin, it cannot effectively inhibit the dissolution of metal ions and provide a good conductive network. If the conductive material coating layer is too thick, it will affect the lithium ion transmission and reduce the lithium supplement component, thereby affecting the lithium supplement capacity. The above thickness can fully play the role of hindering metal dissolution and improve the conductivity of the lithium supplement composite material.
[0013] In some embodiments, the lithium-replenishing composite material has a Dv50 particle size of 5 to 10 μm. This particle size further facilitates the full utilization of lithium-replenishing properties and optimizes the battery's cycling performance. The metal catalyst has a Dv50 particle size of 0.5 to 5 μm. A particle size that is too small makes synthesis difficult, making industrialization difficult, and can easily lead to poor stability of the catalytic material itself. A particle size that is too large can weaken the catalytic activity of the metal catalyst. The thickness of the conductive material-containing coating layer is 5 to 50 nm. This thickness can further hinder metal dissolution and improve the conductivity of the lithium-replenishing composite material.
[0014] In some embodiments, the decomposition voltage of the lithium-supplementing composite material is 4.12V~4.35V. The lithium-supplementing composite material has a lower decomposition voltage, so that the organic lithium-supplementing agent can exert more capacity at low potential, thereby achieving the lithium-supplementing effect while avoiding the irreversible damage of the positive electrode active material structure and the electrolyte caused by high potential.
[0015] In some embodiments, the mass ratio of the metal catalyst to the lithium supplement agent is (1-30):100. If the ratio of the metal catalyst in the composite lithium supplement agent is too low, it cannot fully catalyze the delithiation of the lithium supplement agent, while if the ratio is too high, the lithium supplement component will be reduced, affecting the lithium supplement capacity. Under the above ratio, the ratio is moderate.
[0016] In some embodiments, the mass ratio of the metal catalyst to the lithium replenisher is (5-10):100. The above ratio is conducive to fully catalyzing the delithiation of the lithium replenisher, and the lithium replenishing capacity is relatively high.
[0017] In a second aspect, the present application proposes a method for preparing the lithium-supplemented composite material described in the above embodiment, comprising the following steps:
[0018] dissolving an organic lithium supplement agent in a solvent to prepare a solution, and adding a metal catalyst to the solution to obtain a suspension;
[0019] Recrystallizing the suspension to obtain a core;
[0020] A coating layer containing a conductive material is prepared on the outer side of the core to obtain a lithium-supplementing composite material.
[0021] The preparation method of the lithium-supplementing composite material proposed in this application synthesizes the lithium-supplementing composite material by an in-situ recrystallization method. On the one hand, the lithium-supplementing agent and the metal catalyst can be fully mixed and evenly mixed, and on the other hand, the particle size of the lithium-supplementing composite material can be controlled.
[0022] In a third aspect, the present application proposes a positive electrode sheet, comprising the lithium-supplemented composite material described in the above embodiments or the lithium-supplemented composite material obtained by the preparation method described in the above embodiments.
[0023] In some embodiments, the positive electrode sheet includes a positive electrode material, and the positive electrode material includes the lithium-supplementing composite material. Directly coating the lithium-supplementing composite material in the above embodiment with the positive electrode material is compatible with existing processes and has high safety.
[0024] In some embodiments, the positive electrode material also includes a positive electrode active material, and the mass proportion of the lithium-supplementing composite material in the positive electrode material is 0.5% to 20%. The proportion of the lithium-supplementing composite material in the positive electrode material will affect the life and energy density of the battery. When the proportion of the lithium-supplementing composite material is too low, the amount of lithium ions supplemented during the first charging process will be too small to meet the consumption of active lithium ions during the long-term cycle of the battery, and a long life cannot be achieved; when the proportion of the lithium-supplementing material is too high, the proportion of active materials used for later reversible cycles will decrease, thereby affecting the energy density of the battery. Therefore, it is particularly important to select a suitable proportion of lithium-supplementing agents to balance the life and energy density of the battery. Under the above ratio, it can meet the consumption of active lithium ions during the long-term cycle of the battery without affecting the energy density of the battery.
[0025] In some embodiments, the lithium-replenishing composite material accounts for 1% to 10% by weight of the positive electrode material, which is more effective in replenishing lithium and improving battery energy density.
[0026] In a fourth aspect, the present application provides a separator, comprising the lithium-supplemented composite material described in the above embodiments or the lithium-supplemented composite material obtained by the preparation method described in the above embodiments.
[0027] In a fifth aspect, the present application proposes a secondary battery comprising the positive electrode sheet described in the above embodiment or the isolation membrane in the above embodiment.
[0028] In a sixth aspect, the present application proposes an electrical device comprising the secondary battery described in the above embodiment. Beneficial effects
[0029] The material of the core includes an organic lithium replenisher and a metal catalyst. The organic lithium replenisher provides a lithium source for lithium replenishment. During the first cycle of charging of the battery, the organic lithium replenisher releases lithium ions to replenish the negative electrode, and the remaining components are converted into gas and discharged from the battery. There is no residue after the lithium replenishment, which will not affect the mass energy density and subsequent performance of the battery. The presence of the metal catalyst can reduce the decomposition potential of the organic lithium replenisher, thereby allowing the organic lithium replenisher to exert more capacity at a low potential, achieving the lithium replenishment effect while avoiding the irreversible damage of the positive electrode active material structure and the electrolyte by the high potential. The conductive material coating layer is at least partially coated on the outside of the core, which can inhibit the dissolution of the metal in the metal catalyst. At the same time, it can also improve the conductive properties of the lithium replenishing composite material, thereby optimizing the cycle performance of the battery. The lithium replenishing composite material proposed in this application has excellent lithium replenishing performance and can optimize the cycle performance of the battery through the coating layer containing the conductive material and the core provided in the coating layer containing the conductive material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.
[0031] FIG1 is a schematic structural diagram of a lithium-supplementing composite material according to an embodiment of the present application;
[0032] FIG2 is a voltage-specific capacity curve diagram of the batteries of Example 3 and Comparative Example 2 of the present application;
[0033] FIG3 is a cycle performance diagram of the batteries of Example 3 and Comparative Example 2 of the present application.
[0034] The accompanying drawings in the specific implementation manner are as follows:
[0035] Contains a coating layer 1 of a conductive material, a lithium supplement 2, and a metal catalyst 3.
[0036] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings and in conjunction with the embodiments. Modes for Carrying Out the Invention
[0037] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.
[0038] It should be noted that, in the embodiments, those without specifying specific conditions, are carried out according to conventional conditions or the conditions recommended by the manufacturer. Those for reagents or instruments used that do not specify the manufacturer are conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes schemes A, B, or A and B that meet the same time. In addition, the technical solutions between the various embodiments can be combined with each other, but must be based on those of ordinary skill in the art. When the combination of the technical solutions is contradictory or cannot be realized, it should be considered that the combination of such technical solutions does not exist and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work belong to the scope of protection of the present invention.
[0039] During the first cycle of lithium-ion energy storage devices, irreversible capacity loss occurs due to the formation of a solid electrolyte interface (SEI) at the negative electrode interface. This reduction in active lithium content leads to a decrease in the energy density of the lithium-ion energy storage device. To address the problem of reduced battery capacity caused by irreversible lithium loss during the first charge and discharge process, pre-lithiation lithium replenishment technology has become the preferred choice among many technologies. Existing pre-lithiation lithium replenishment technologies mainly use active metallic lithium, but the lithium replenishment effect is not good.
[0040] Existing pre-lithiation lithium replenishment technologies mainly include negative electrode pre-lithiation and positive electrode pre-lithiation. Among them, negative electrode lithium replenishment mainly uses active metallic lithium, which has strict requirements on manufacturing process and operating environment, and is accompanied by safety hazards, which is not conducive to large-scale production; positive electrode pre-lithiation technology mainly coats the lithium material directly with the positive electrode material, which is better compatible with existing processes and has high safety.
[0041] Positive electrode pre-lithiation materials include inorganic lithium-rich materials and organic lithium-supplementing materials. The commercial application of inorganic lithium-rich materials is hampered by their poor air stability and residual issues. Organic lithium-supplementing materials offer advantages such as high theoretical capacity, good air stability, and low cost, making them promising candidates for practical positive electrode lithium-supplementing materials. However, organic lithium-supplementing materials used directly as additives typically have high decomposition potentials, hindering lithium ion release. Furthermore, side reactions between the electrode and the electrolyte are more likely to occur at high potentials, leading to poor cycling performance.
[0042] Based on this, researchers in this field have made improvements. For example, a composite lithium-supplementing material comprises an organic lithium salt and a metal catalyst. The organic lithium-supplementing material is a lithium carbon oxide, and the metal catalyst is a transition metal compound with a heterojunction structure as provided by the present invention. Compared to using a single transition metal oxide or transition metal nitride as the metal catalyst, this can significantly reduce the decomposition potential of the organic lithium salt, increase the lithium-supplementing capacity, and improve battery cycling performance. Another example is an inorganic lithium-supplementing material (one or more of lithium peroxide, lithium oxide, lithium sulfate, lithium borate, lithium metasilicate, lithium orthosilicate, and lithium phosphate). After a conductive material is composited onto the surface of the lithium-supplementing material, an inorganic sulfide is used as a reducing agent, and a metal or non-metallic catalyst is added. This can effectively reduce the potential at which the lithium-supplementing material exerts its capacity.
[0043] However, after a large number of experiments, the inventors found that the above solution still has certain shortcomings: first, it does not provide a solution to the problem of metal dissolution of metal catalysts containing transition metals during the subsequent use of the battery; second, it does not improve the fact that the lithium supplement has poor conductivity.
[0044] Based on this, after repeated experimental research and consulting a large amount of information, the inventor wanted to solve the two problems of lithium supplement conductivity and metal dissolution at the same time. He was surprised to find that after mixing the lithium supplement and the metal catalyst, coating them in a conductive material to make a composite material similar to a core-shell structure, the above two problems can be solved at the same time.
[0045] Specifically, this application proposes a lithium-supplementing composite material. Referring to FIG1 , the lithium-supplementing composite material includes a core and a coating layer 1 comprising a conductive material disposed outside the core and at least partially covering the core. The core comprises a lithium-supplementing agent 2 and a metal catalyst 3. The lithium-supplementing agent 2 comprises an organic lithium-supplementing agent. The lithium-supplementing composite material proposed in this application has the following beneficial effects:
[0046] The material of the core includes an organic lithium replenisher and a metal catalyst. The organic lithium replenisher provides a lithium source for lithium replenishment. During the first cycle of charging of the battery, the organic lithium replenisher releases lithium ions to replenish the negative electrode, and the remaining components are converted into gas and discharged from the battery. There is no residue after the lithium replenishment, which will not affect the mass energy density and subsequent performance of the battery. The presence of the metal catalyst can reduce the decomposition potential of the organic lithium replenisher, thereby allowing the organic lithium replenisher to exert more capacity at a low potential, achieving the lithium replenishment effect while avoiding the irreversible damage of the positive electrode active material structure and the electrolyte by the high potential. The conductive material coating layer is at least partially coated on the outside of the core, which can inhibit the dissolution of metal in the metal catalyst. At the same time, it can also improve the conductive properties of the lithium replenishing composite material, thereby improving the lithium replenishment capacity and service life of the battery. The lithium replenishing composite material proposed in this application has excellent lithium replenishing performance and can optimize the cycle performance of the battery through the coating layer containing the conductive material and the core provided in the coating layer containing the conductive material.
[0047] It can be understood that the above-mentioned lithium-supplementing composite material proposed in this application, the coating layer containing the conductive material can completely cover the core to form a core-shell structure, or can partially cover it. Both of the above situations are within the scope of protection of this application. In the embodiment of this application, the coating layer containing the conductive material completely covers the core to form a core-shell structure, which is more conducive to inhibiting the metal dissolution of the metal catalyst and improving the conductivity of the lithium-supplementing composite material.
[0048] In addition, the metal catalyst in the present application is a catalyst containing metal elements, including metal elements, metal compounds and alloys of multiple metals, etc. All of the above substances are within the scope of protection of the present application.
[0049] In some embodiments, referring to FIG. 1 , it can be seen that the lithium supplement agent 2 and the metal catalyst 3 are uniformly mixed in the core. This is conducive to further exerting the role of the catalyst, reducing the decomposition potential of the organic lithium supplement agent, thereby allowing the organic lithium supplement agent to exert more capacity at a low potential, achieving the lithium supplement effect while avoiding irreversible damage to the positive electrode active material structure and the electrolyte caused by high potential.
[0050] In some embodiments, the organic lithium supplement includes Li2C2O4, Li2C4O4, Li2C3O5, Li2C4O6, (Li2C2O2N2) n At least one of the above organic lithium replenishers has a high decomposition potential. During the first cycle of charging of the battery, lithium ions are released to replenish lithium to the negative electrode, and the remaining components simultaneously generate gases such as carbon monoxide, carbon dioxide, nitrogen or nitrogen oxides, which are discharged from the battery. There is no residue after the lithium replenishment, and it will not affect the mass energy density and subsequent performance of the battery.
[0051] It is understandable that (Li2C2O2N2) n The structural formula is [COCON(Li)N(Li)] n The preparation method is as follows: first, oxalyl dihydrazide ([CONHNH2]2) and oxalyl chloride are added to a dry acetonitrile suspension, and pyridine is used as a proton scavenger to obtain a light yellow polymer [COCONHNH] through a polycondensation reaction. n Then, it was added to a methoxylithium solution in anhydrous DMF, stirred, centrifuged and washed twice with anhydrous ethanol to obtain bright yellow [COCON(Li)N(Li)] n The released lithium ions replenish the negative electrode with lithium, and the remaining components generate gases such as N2, CO2 and CO.
[0052] In some embodiments, the metal catalyst comprises at least one of a transition metal oxide, a transition metal nitride, and a transition metal carbide. Transition metals have unfilled valence shell d orbitals, which easily deform their electron clouds. Based on the 18-electron rule, their properties differ significantly from those of other elements. Due to the presence of empty d orbitals, transition metals readily form complexes. Metal elements utilize hybrid orbitals to accept electrons to achieve a stable state of 16 or 18 electrons, making them suitable for use as metal catalysts. Therefore, using at least one of a transition metal oxide, a transition metal nitride, and a transition metal carbide as a metal catalyst exhibits excellent catalytic effects.
[0053] In some embodiments, the transition metal comprises at least one of Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, In, W, Zr, Ta and W, and the general formulas of the transition metal oxide, transition metal nitride and transition metal carbide are M, x O y , MxN y , M x C y , wherein M is one or more transition metals selected from the group consisting of Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, In, W, Zr, Ta, and W, and 0<x≤3, 0<y≤5; using at least one of the above transition metals can reduce the decomposition potential of the organic lithium replenisher, thereby allowing the organic lithium replenisher to exert greater capacity at a low potential, thereby achieving a lithium replenishment effect while avoiding irreversible damage to the positive electrode active material structure and the electrolyte caused by high potential.
[0054] In some embodiments, the conductive coating layer comprises at least one of an organic conductive polymer and conductive carbon. Using such a conductive coating layer can reduce the dissolution of transition metals while enhancing the overall conductivity of the material, thereby improving the battery's lithium replenishment capacity and service life.
[0055] In some embodiments, the material of the coating layer containing the conductive material includes an organic conductive polymer, and the organic conductive polymer includes at least one of polyaniline, polypyrrole, and polythiophene. Polyaniline is a type of conductive polymer material obtained from aniline monomer through chemical oxidation polymerization or electrochemical polymerization. After doping, polyaniline has conductivity, and it also has photoelectric conversion properties and nonlinear optical properties. The electrical activity of polyaniline comes from the π electron conjugated structure in the molecular chain: as the π electron system in the molecular chain expands, the π bonding state and the π* antibonding state form the valence band and conduction band respectively. This non-localized π electron conjugated structure can form P-type and N-type conductive states after doping. Unlike the doping mechanism of other conductive polymers that produce cationic vacancies under the action of oxidants, the number of electrons in the doping process of polyaniline does not change, but is generated by the decomposition of the doped proton acid to produce H + and counter anions (such as Cl - , sulfate, phosphate, etc.) enter the main chain and combine with the nitrogen atoms in the amine and imine groups to form polar and bipolar delocalized into the π bonds of the entire molecular chain, thereby making polyaniline exhibit high conductivity. Polyaniline has the characteristics of high charge storage capacity, good stability to oxygen and water, good electrochemical performance, low density and reversible oxidation / reduction characteristics. It can serve as both a conductive matrix and an active material in composite electrodes. Polypyrrole is a common conductive polymer with high conductivity, good environmental stability, reversible electrochemical redox characteristics and strong charge storage capacity. It is an ideal electrode material for polymer secondary batteries. Polythiophene is a common conductive polymer. The polythiophene obtained by electrochemical polymerization in a boron trifluoride ether complex has a strength greater than that of metallic aluminum. Using at least one of the above organic conductive polymers further reduces metal dissolution and improves conductivity.
[0056] In some embodiments, the material of the coating layer containing the conductive material includes conductive carbon, and the conductive carbon includes at least one of graphene, carbon nanotubes, acetylene black, Super P, Ketjen black and organic-derived carbon. Graphene is a new material in which carbon atoms connected by sp² hybridization are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Graphene has excellent optical, electrical and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine and drug delivery. It is considered to be a revolutionary material in the future; carbon nanotubes, as one-dimensional nanomaterials, are light in weight, have perfect hexagonal structures, and have many abnormal mechanical, electrical and chemical properties; acetylene black is acetylene with a purity of more than 99% obtained by decomposition and purification of by-product gas during pyrolysis of calcium carbide or naphtha (raw gasoline), and is obtained by continuous pyrolysis. Compared with furnace carbon black, its crystallization and secondary structure are more developed, so its conductivity and liquid absorption are also better, with less impurities such as heavy metals and less loss caused by self-discharge; Super P P (SP) is a conductive carbon black prepared by the furnace method (MMM method). It is composed of primary particles (primary structure) with a diameter of about 40nm agglomerated into primary aggregates (secondary structure) of 150~200nm, and then processed through soft agglomeration and artificial compression. The overall shape is grape chain; the role of SP in lithium-ion batteries is more to disperse primary aggregates of 150~200nm around the active material to form a multi-branched conductive network, thereby reducing the physical internal resistance of the battery and improving electronic conductivity; Ketjen black (Ketjen black) is a carbon black produced by a very original special production process. Compared with ordinary conductive carbon black, Ketjen black only requires a very low addition amount to achieve high conductivity, so Ketjen black has always been the best among conductive carbon blacks; using at least one of the above-mentioned conductive carbons can further reduce metal dissolution and improve conductive performance.
[0057] In some embodiments, the Dv50 particle size of the lithium-supplementing composite material is 2 to 30 μm, for example, it can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 17 μm, 19 μm, 20 μm, 22 μm, 24 μm, 25 μm, 27 μm, 29 μm, 30 μm, etc. If the Dv50 particle size of the lithium-supplementing composite material is too small, the slurry will easily agglomerate and gel, the viscosity will increase, and the solid content will decrease. If the particle size is too large, the polarization of the lithium ion extraction reaction in the lithium-supplementing agent will increase, thereby reducing the lithium-supplementing efficiency. When the particle size is above, it is conducive to fully exerting the lithium-supplementing performance and optimizing the cycle performance of the battery. The Dv50 particle size of the metal catalyst is 0.1 to 10 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. If the particle size is too small, the synthesis is difficult and is not conducive to industrialization, and it is easy to cause the stability of the catalytic material itself to deteriorate; if the particle size is too large, the catalytic activity of the metal catalyst will be weakened. The thickness of the coating layer containing the conductive material is 2 to 100 nm, for example, 2 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc. The thickness of the coating layer containing the conductive material directly affects the coating performance. If the conductive material coating layer of the composite lithium supplement shell is too thin, it cannot effectively inhibit the dissolution of metal ions and provide a good conductive network. If the conductive material coating layer is too thick, it will affect the lithium ion transmission and reduce the lithium supplement component, thereby affecting the lithium supplement capacity. The above thickness can fully play the role of hindering metal dissolution and improve the conductivity of the lithium supplement composite material.
[0058] In some embodiments, the Dv50 particle size of the lithium-supplementing composite material is 5 to 10 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. When the particle size is above, it is further conducive to fully exerting the lithium-supplementing performance and optimizing the cycle performance of the battery. The Dv50 particle size of the metal catalyst is 0.5 to 5 μm, such as 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc. If the particle size is too small, the synthesis is difficult and not conducive to industrialization, and it is easy to cause the stability of the catalytic material itself to deteriorate; if the particle size is too large, the catalytic activity of the metal catalyst will be weakened. The thickness of the coating layer containing the conductive material is 5 to 50 nm, such as 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc. The above thickness can further play a role in hindering the dissolution of the metal and improving the conductivity of the lithium-supplementing composite material.
[0059] In some embodiments, the decomposition voltage of the lithium-supplementing composite material is 4.12V~4.35V, for example, it can be 4.12V, 4.15V, 4.18V, 4.2V, 4.23V, 4.25V, 4.27V, 4.3V, 4.31V, 4.35V, etc. The lithium composite material has a lower decomposition voltage, so that the organic lithium-supplementing agent can exert more capacity at low potential, thereby achieving the lithium-supplementing effect while avoiding the irreversible damage of the positive electrode active material structure and the electrolyte caused by high potential.
[0060] In some embodiments, the mass ratio of the metal catalyst to the lithium supplement agent is (1-30):100, for example, 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, etc. If the ratio of the metal catalyst in the composite lithium supplement agent is too low, it cannot fully catalyze the delithiation of the lithium supplement agent, while if the ratio is too high, the lithium supplement component will be reduced, affecting the lithium supplement capacity. Under the above ratio, the ratio is moderate.
[0061] In some embodiments, the mass ratio of the metal catalyst to the lithium replenisher is (5-10):100, for example, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, etc. The above ratio is conducive to fully catalyzing the delithiation of the lithium replenisher and having a higher lithium replenishment capacity.
[0062] This application does not limit the preparation method of the lithium-replenishing composite material. The uniform compounding of the lithium-replenishing agent and the transition metal catalyst is a prerequisite for the full catalytic effect of the transition metal catalyst. Physical mixing methods, including grinding, sand milling, and ball milling, are simple to operate and can achieve a relatively uniform compounding of the lithium-replenishing agent and the transition metal catalyst while simultaneously reducing the particle size of the material. However, this effect is limited and the particle size cannot be controlled. In contrast, the in-situ method of recrystallization to synthesize the composite lithium-replenishing agent allows for a thorough and uniform mixing of the lithium-replenishing agent and the metal catalyst while also controlling the particle size of the composite material.
[0063] In a second aspect, the present application proposes a method for preparing the lithium-supplemented composite material described in the above embodiment, comprising the following steps:
[0064] dissolving an organic lithium supplement agent in a solvent to prepare a solution, and adding a metal catalyst to the solution to obtain a suspension;
[0065] Recrystallizing the suspension to obtain a core;
[0066] A coating layer containing a conductive material is prepared on the outer side of the core to obtain a lithium-supplementing composite material.
[0067] The preparation method of the lithium-supplementing composite material proposed in this application synthesizes the lithium-supplementing composite material by an in-situ recrystallization method. On the one hand, the lithium-supplementing agent and the metal catalyst can be fully mixed and evenly mixed, and on the other hand, the particle size of the lithium-supplementing composite material can be controlled.
[0068] Those skilled in the art will understand that, in the above-mentioned method of a specific embodiment, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. In addition, other steps may be performed between each step.
[0069] The preparation method of the lithium-supplementing composite material proposed in this application has all the beneficial effects of the above-mentioned lithium-supplementing composite materials, which will not be described in detail here.
[0070] In a third aspect, the present application proposes a positive electrode sheet, comprising the lithium-supplemented composite material described in the above embodiments or the lithium-supplemented composite material obtained by the preparation method described in the above embodiments.
[0071] In some embodiments, the positive electrode sheet includes a positive electrode material, and the positive electrode material includes the lithium-supplementing composite material. Directly coating the lithium-supplementing composite material in the above embodiment with the positive electrode material is compatible with existing processes and has high safety.
[0072] In some embodiments, the positive electrode material further includes a positive electrode active material, and in the positive electrode material, the mass proportion of the lithium-supplementing composite material is 0.5% to 20%, for example, it can be 0.5%, 1%, 3%, 5%, 10%, 15%, 18%, 20%, etc. The proportion of the lithium-supplementing composite material in the positive electrode material will affect the life and energy density of the battery. When the proportion of the lithium-supplementing composite material is too low, the amount of lithium ions supplemented during the first charge will be too small to meet the consumption of active lithium ions during the long-term cycle of the battery, and a long life cannot be achieved; when the proportion of the lithium-supplementing material is too high, the proportion of active materials used for the later reversible cycle will decrease, thereby affecting the energy density of the battery. Therefore, it is particularly important to select a suitable proportion of lithium-supplementing agents to balance the life and energy density of the battery. Under the above proportion, it can meet the consumption of active lithium ions during the long-term cycle of the battery without affecting the energy density of the battery.
[0073] In some embodiments, the lithium-replenishing composite material accounts for 1% to 10% by weight of the positive electrode material, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., which is more effective in replenishing lithium and improving battery energy density.
[0074] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the binder of the first aspect of the present application.
[0075] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0076] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0077] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.3 Mn 0.2 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0078] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder described in the first aspect of the present application, and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0079] The positive electrode sheet proposed in this application includes the lithium-supplementing composite material in the above embodiment, and has all the beneficial effects of the above lithium-supplementing composite material, which will not be described in detail here.
[0080] In a fourth aspect, the present application provides a separator, comprising the lithium-supplemented composite material described in the above embodiments or the lithium-supplemented composite material obtained by the preparation method described in the above embodiments.
[0081] Specifically, the isolation membrane includes a base membrane and a coating layer coated on the base membrane. The coating layer may also include a glue layer, a ceramic layer, etc. The lithium-replenishing composite material is coated on the side of the isolation membrane close to the positive electrode plate, which can also play the role of lithium replenishment.
[0082] The isolation membrane proposed in the present application, including the lithium-supplementing composite material in the above embodiment, has all the beneficial effects of the above lithium-supplementing composite material, which will not be described in detail here.
[0083] In a fifth aspect, the present application proposes a secondary battery comprising the positive electrode sheet described in the above embodiment or the isolation membrane in the above embodiment.
[0084] Typically, a battery cell consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0085] The preparation of battery cells can be carried out by methods commonly used in the art. For example, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process, and then the electrolyte is injected into the electrode assembly and sealed to produce a battery cell.
[0086] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0087] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0088] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0089] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0090] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0091] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0092] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0093] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the battery cell may be a soft shell, such as a pouch-type soft shell. The soft shell may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0094] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape.
[0095] The specific forms of the battery may be a battery module and a battery pack. The number of battery cells contained in a battery module may be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0096] A battery module is a system that electrically connects a number of secondary batteries and houses them in a frame to protect them from external shock, heat, and vibration. A typical battery module consists of two end plates, with multiple battery cells (lithium-ion batteries) arranged between them. The end plate with the module's output terminals is called the output terminal plate, while the end plate without these terminals is called the non-output terminal plate.
[0097] In some battery production and processing technologies, multiple battery cells are first integrated into battery modules, and then the battery modules are encapsulated in a battery casing to form a battery pack. A battery pack can encapsulate multiple battery modules in one row, or multiple rows of multiple battery modules. The arrangement of multiple rows of multiple battery modules can be double-row multiple-columns, multiple rows of double-columns, multiple rows of multiple-columns, etc. Taking a battery pack encapsulating double-row multiple-column battery modules as an example, the first end plate in each column is generally the head output extreme plate, the two adjacent end plates between the two rows of battery modules are the middle non-output extreme plates, and the last end plate in each column is the tail non-output extreme plate. The head output extreme plate and one of the middle non-output extreme plates belong to the first row of battery modules, and one of the middle non-output extreme plates and the tail output extreme plate belong to the second row of battery modules.
[0098] The secondary battery proposed in this application, including the lithium-supplementing composite material in the above embodiments, has all the beneficial effects of the above lithium-supplementing composite material, which will not be described in detail here.
[0099] In a sixth aspect, the present application proposes an electrical device comprising the secondary battery described in the above embodiment.
[0100] The electrical devices proposed in this application include but are not limited to: mobile phones, portable devices, laptops, electric vehicles, ships, spacecraft, electric toys and electric tools, etc. For example, spacecraft include airplanes, rockets, space shuttles and spacecraft, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric vehicle toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting power tools, grinding power tools, assembly power tools and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.
[0101] The electrical device proposed in this application, including the lithium-supplementing composite material in the above embodiment, has all the beneficial effects of the above lithium-supplementing composite material, which will not be described in detail here.
[0102] The technical solutions of the present invention are further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0103] The parameter settings of the lithium-supplementing composite materials of the embodiment and comparative example are shown in Table 1 below:
[0104] Table 1 Parameter settings of lithium-supplementing composite materials of Examples and Comparative Examples Metal catalysts Mass proportion of lithium-supplemented composite materials Mass ratio of metal catalyst to lithium supplement lithium supplements Coating containing conductive material Dv50 particle size of lithium-supplemented composite materials / μm Metal catalyst Dv50 particle size / μm Thickness of the coating layer containing conductive material / nm Example 1 Cobalt nitride 0.01 0.07 Li2C2O4 organic-derived carbon 10 5 50 Example 2 Cobalt nitride 0.03 0.07 Li2C2O4 organic-derived carbon 10 5 50 Example 3 Cobalt nitride 0.05 0.07 Li2C2O4 organic-derived carbon 10 5 50 Example 4 Cobalt nitride 0.10 0.07 Li2C2O4 Organic-derived carbon 10 5 50 Example 5 Cobalt nitride 0.05 0.02 Li2C2O4 Organic-derived carbon 10 5 50 Example 6 Cobalt nitride 0.05 0.10 Li2C2O4 Organic-derived carbon 10 5 50 Example 7 Cobalt nitride 0.05 0.20 Li2C2O4 Organic-derived carbon 10 5 50 Example 8 Cobalt nitride 0.20 0.07 Li2C2O4 Organic-derived carbon 10 5 50 Example 9 Cobalt nitride 0.05 0.30 Li2C2O4 Organic-derived carbon 10 5 50 Example 10 Cobalt nitride 0.05 0.05 Li2C2O4 Organic-derived carbon 10 5 50 Example 11 Cobalt oxide 0.05 0.07 Li2C2O4 Organic-derived carbon 10 5 50 Example 12 Molybdenum carbide 0.05 0.07 Li2C2O4 Organic-derived carbon 10 5 50 Example 13 Iron nitride 0.05 0.07 Li2C2O4 Organic-derived carbon 10 5 50 Example 14 Cobalt nitride 0.05 0.07 Li2C2O4 polyaniline 10 5 50 Example 15 Cobalt nitride 0.05 0.07 Li2C2O4 graphene 10 5 50 Example 16 Cobalt nitride 0.05 0.07 Li2C2O4 Organic-derived carbon 2 1 50 Example 17 Cobalt nitride 0.05 0.07 Li2C2O4 Organic-derived carbon 30 5 50 Example 18 Cobalt nitride 0.05 0.07 Li2C2O4 Organic-derived carbon 10 0.1 50 Example 19 Cobalt nitride 0.05 0.07 Li2C2O4 Organic-derived carbon 15 9.5 50 Example 20 Cobalt nitride 0.05 0.07 Li2C2O4 Organic-derived carbon 10 5 2 Example 21 Cobalt nitride 0.05 0.07 Li2C2O4 Organic-derived carbon 10 5 100 Comparative Example 1 - - - - Organic-derived carbon 10 5 50 Comparative Example 2 - 0.05 0 Li2C2O4 Organic-derived carbon 10 - 50 Comparative Example 3 Cobalt nitride 0.05 0.07 Li2C2O4 - 10 5 -
[0105] [Combination of lithium supplement and metal catalyst]
[0106] Taking Example 3 as an example, at 25°C, 10 g of lithium oxalate (Li2C2O4) was dissolved in 100 g of deionized water, and then 0.7 g of cobalt nitride with an average particle size D50 of 2 μm was added thereto, and ultrasonic dispersion was carried out for 1 hour to obtain a lithium oxalate suspension containing cobalt nitride, which was recorded as solution A; the above solution A was slowly added dropwise to 120 g of anhydrous ethanol, and stirred at a speed of 500 rpm. After all the solution A was added, stirring was continued for 30 minutes. After standing for 1 hour, the solid phase component was filtered and collected, and dried in a vacuum oven at 80°C for 12 hours to obtain a lithium oxalate and cobalt nitride composite lithium supplement material.
[0107]
Conductive layer coating
[0108] The lithium oxalate and cobalt nitride composite lithium supplement material obtained above was evenly mixed with 5g of polyvinyl alcohol, placed in a tube furnace, and sintered at 400°C for 2h with argon gas to obtain a composite lithium supplement material with a core of lithium oxalate / cobalt nitride composite material and an outer shell of a carbon layer.
[0109]
Preparation of positive electrode sheet
[0110] The core-shell structured composite lithium supplement material, lithium iron phosphate material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) obtained above are mixed in an N-methylpyrrolidone (NMP) solvent system in a weight ratio of 5:92:1:2 to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode current collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0111]
Preparation of negative electrode sheet
[0112] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a weight ratio of 96.2:0.8:0.8:1.2, and mixed evenly to prepare the negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0113] Preparation of electrolyte
[0114] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7, 12.5% LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to obtain the electrolyte of Example 3.
[0115]
Isolation film
[0116] Polypropylene film is used as the isolation film.
[0117] Preparation of lithium-ion batteries
[0118] The positive electrode sheet, separator, and negative electrode sheet of Example 3 were stacked in order, with the separator positioned between the positive and negative electrode sheets to provide isolation. The cells were then wound to obtain a bare cell. The tabs were welded to the bare cell and placed in an aluminum casing. The cells were then baked at 80°C to remove moisture. The electrolyte was then injected and sealed to obtain an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the lithium-ion battery product of Example 3.
[0119] The lithium-ion battery products of the comparative example and the remaining embodiments were prepared in the same manner as described above, with the only difference being that the corresponding parameters were different.
[0120] In addition, in the embodiment where the material of the coating layer containing the conductive material is not organic-derived carbon, it does not need to be fired at a high temperature in a tube furnace and can be directly mixed and ground.
[0121] Wherein, there is no lithium supplement in Comparative Example 1, no metal catalyst in Comparative Example 2, and no coating layer containing a conductive material in Comparative Example 3.
[0122]
Battery performance test
[0123] 1. Battery capacity retention test
[0124] Taking Example 3 as an example, the battery capacity retention rate test process is as follows: at 60°C, the formed battery corresponding to Example 3 is charged to 3.65V at a constant current of 1 / 3C, then charged to 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged to the discharge cut-off voltage at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery mentioned above, and at the same time record the discharge capacity Cn of the battery after the nth cycle. The battery capacity retention rate after each cycle is Pn=Cn / C0*100%. In this test process, the first cycle corresponds to n=1, the second cycle corresponds to n=2, and... the 100th cycle corresponds to n=100. The battery capacity retention rate data corresponding to Example 3 in Table 1 are the data measured after 100 cycles under the above test conditions, that is, the value of P100. The test process of Comparative Example 1 and other embodiments is the same as above.
[0125] 2. Battery volume energy density test
[0126] Measure the internal dimensions of the battery case (length a, width b, and height c). Measure the discharge energy (E0) of each battery when it is charged at a 1C rate to a voltage of 3.65V at room temperature and then discharged at a 1C rate to a voltage of 2.5V.
[0127] Battery volume energy density = E0 / (a×b×c).
[0128] 3. First charge capacity test
[0129] Taking Example 3 as an example, before assembling the battery, weigh the mass of the positive electrode sheet and calculate the total mass m of the lithium iron phosphate and the composite lithium supplement. Select appropriate charging conditions to charge the assembled battery to 4.5V for the first time. The resulting charging capacity is recorded as Q, then:
[0130] The battery's initial charge capacity in grams = Q / m.
[0131] 4. Lithium supplement decomposition voltage test
[0132] After the first week of charging, record the voltage (V) and capacity (Q) data of the charging process, and plot dQ / dV against V. Record the potential corresponding to the oxidation peak. The peak potential greater than 3.65V is the decomposition voltage of the lithium supplement.
[0133] The measurement results are shown in Table 2:
[0134] Table 2 Performance measurement of lithium-supplemented composite materials of Examples and Comparative Examples Energy density Wh / L Decomposition voltage of lithium-supplemented composite materials (V) First charge capacity (mAh / g) Capacity retention rate after 100 cycles at 60℃ Example 1 182 4.2V 164.4 96.1% Example 2 186 4.2V 171.2 96.9% Example 3 176 4.2V 178.5 98.1% Example 4 167 4.25V 195.1 99.2% Example 5 174 4.35V 177.6 97.5% Example 6 175 4.16V 178.1 97.8% Example 7 174 4.13V 178.2 97.1% Example 8 158 4.21 205.3 99.6% Example 9 172 4.12 177.5 95.6% Example 10 176 4.22V 177.9 97.2% Example 11 176 4.35V 178.0 98.0% Example 12 176 4.3V 178.2 97.6% Example 13 175 4.4V 177.2 97.0% Example 14 174 4.32V 176.2 96.9% Example 15 176 4.15V 179.5 98.2% Example 16 170 4.18V 179.1 98.4% Example 17 173 4.31V 177.1 97.2% Example 18 178 4.21V 178.2 98.5% Example 19 174 4.25V 176.7 97.5% Example 20 173 4.32V 175.4 96.1% Example 21 176 4.18V 178.1 97.8% Comparative Example 1 180 / 161.2 93.8% Comparative Example 2 172 4.7V 152.3 92.6% Comparative Example 3 172 4.4V 174.5 94.3%
[0135] As can be seen from Table 2, the lithium-supplementing composite material of the embodiment of the present application has better energy density, lithium-supplementing agent decomposition voltage, initial charge gram capacity, and capacity retention rate after 100 cycles at 60°C than the comparative example. It can be seen that the coating layer containing the conductive material, the lithium-supplementing agent, and the metal catalyst of the present application are indispensable and play an important role in replenishing lithium and improving the cycle performance of the battery.
[0136] The electronic conductivity of the lithium-supplemented composite materials of Example 3 and Comparative Example 3 were 7.9×10 -3 s / m and 3.8×10 -5 s / m, it can be seen that the presence of the conductive material coating layer can improve the conductive properties of the lithium-replenishing composite material, thereby improving the lithium-replenishing capacity and service life of the battery.
[0137] The batteries of Example 3 and Comparative Example 2 were charged on a battery charge and discharge tester, and the voltage-charge specific capacity graph was measured and derived to obtain Figure 2. It can be seen that no metal catalyst was added to the lithium-supplementing composite material of Comparative Example 2, resulting in a higher decomposition potential of the organic lithium-supplementing agent, while the decomposition potential of Example 3 of the present application was lower, allowing the organic lithium-supplementing agent to exert more capacity at a low potential, achieving a lithium-supplementing effect while avoiding irreversible damage to the positive electrode active material structure and the electrolyte caused by high potential.
[0138] The cycle performance diagrams of the batteries of Example 3 and Comparative Example 2 are shown in FIG3 . It can be seen that the cycle performance of the present application is significantly better than that of Comparative Example 2. It can be seen that the presence of the metal catalyst can simultaneously optimize the cycle performance of the battery.
[0139] In summary, the lithium-supplementing composite material proposed in this application has excellent lithium-supplementing performance through the coating layer containing conductive material and the core arranged in the coating layer containing conductive material, and can also improve the conductive performance of the lithium-supplementing composite material, thereby improving the lithium-supplementing capacity and service life of the battery, and optimizing the cycle performance of the battery.
[0140] The above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Those skilled in the art will readily appreciate that the present invention is susceptible to various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of the present invention.
Claims
1. A lithium-supplementing composite material, characterized in that: The invention comprises an inner core and a coating layer containing a conductive material and arranged outside the inner core and at least partially covering the inner core. The inner core is made of a lithium supplement agent and a metal catalyst. The lithium supplement agent comprises an organic lithium supplement agent.
2. The lithium-supplementing composite material according to claim 1, wherein The organic lithium supplement includes Li2C2O4, Li2C4O4, Li2C3O5, Li2C4O6, (Li2C2O2N2) n At least one of; and / or, The metal catalyst includes at least one of a transition metal oxide, a transition metal nitride and a transition metal carbide; and / or, The material of the coating layer containing conductive material includes at least one of organic conductive polymer and conductive carbon.
3. The lithium-supplementing composite material according to claim 1, wherein The metal catalyst includes at least one of a transition metal oxide, a transition metal nitride, and a transition metal carbide, and the transition metal includes at least one of Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, In, W, Zr, Ta, and W; and / or, The material of the coating layer containing the conductive material includes an organic conductive polymer, and the organic conductive polymer includes at least one of polyaniline, polypyrrole, and polythiophene; and / or, The conductive material-containing coating layer is made of conductive carbon, and the conductive carbon includes at least one of graphene, carbon nanotubes, acetylene black, Super P, Ketjen black, and organic-derived carbon.
4. The lithium-supplementing composite material according to any one of claims 1 to 3, wherein: The Dv50 particle size of the lithium-supplementing composite material is 2-30 μm; and / or, The metal catalyst has a Dv50 particle size of 0.1 to 10 μm; and / or The thickness of the coating layer containing the conductive material is 2 to 100 nm; and / or, The decomposition voltage of the lithium-supplementing composite material is 4.12V-4.35V.
5. The lithium-supplementing composite material according to any one of claims 1 to 4, wherein: The Dv50 particle size of the lithium-supplementing composite material is 5-10 μm; and / or, The metal catalyst has a Dv50 particle size of 0.5 to 5 μm; and / or The thickness of the coating layer containing the conductive material is 5 to 50 nm.
6. The lithium-supplementing composite material according to any one of claims 1 to 5, wherein: The mass ratio of the metal catalyst to the lithium supplement agent is (1-30):100; or, The mass ratio of the metal catalyst to the lithium supplement agent is (5-10):
100.
7. A method for preparing the lithium-supplementing composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: dissolving an organic lithium supplement agent in a solvent to prepare a solution, and adding a metal catalyst to the solution to obtain a suspension; Recrystallizing the suspension to obtain a core; A coating layer containing a conductive material is prepared on the outer side of the core to obtain a lithium-supplementing composite material.
8. A positive electrode plate, characterized in that: The invention comprises the lithium-supplementing composite material according to any one of claims 1 to 6 or the lithium-supplementing composite material obtained by the preparation method according to claim 7.
9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode plate includes a positive electrode material, and the positive electrode material includes the lithium-supplementing composite material.
10. The positive electrode sheet according to claim 9, wherein: The positive electrode material also includes a positive electrode active material, In the positive electrode material, the mass proportion of the lithium-supplementing composite material is 0.5% to 20%; or, In the positive electrode material, the mass proportion of the lithium-supplementing composite material is 1% to 10%.
11. A separator, characterized in that: The invention comprises the lithium-supplementing composite material according to any one of claims 1 to 6 or the lithium-supplementing composite material obtained by the preparation method according to claim 7.
12. A secondary battery, characterized in that: It comprises the positive electrode sheet according to any one of claims 8 to 10 or the separator according to claim 11.
13. An electrical device, characterized in that: The secondary battery according to claim 12 is included.
Citation Information
Cited By
Composite current collector and preparation method and application thereof
CN120657138A